Effects of Rice Straw Variety on Rumen Fermentation, Bacterial Community, and Metabolite Profile - Tanghui Long; Yashi Li; Mengying Li; Kehui Ouyang; Mingren Qu; Ke Pan; Qinghua Qiu (Agriculture)
The objective of this study was to investigate the effects of different rice varieties on in vitro rumen fermentation characteristics, microbial community, and metabolite profile of rice straw. The inbred variety Zhongjiazao 17 (Z17) and the hybrid variety Ruiliangyou 1053 (R1053) were selected as the two test varieties. Each variety was subjected to in vitro rumen fermentation for 72 h, with five replicates conducted for each. The results showed that R1053 had higher values in total gas production, in vitro dry matter digestibility, total volatile fatty acids (VFA), and individual VFA compared to Z17. Additionally, R1053 exhibited higher values in rumen microbial diversity indices, including Chao1, observed species, PD whole tree, and Shannon index, compared to Z17. The Z17 group had higher relative abundances of Verrucomicrobiota, Chloroflexi, Saccharofermentans, Probable genus 10, and Lachnospiraceae AC2044 group. In contrast, the R1053 group had higher relative abundance of Patescibacteria. Analysis of similarities (ANOSIM) confirmed a significant difference between the Z17 and R1053 groups (R = 0.8160, p = 0.005). Metabolomic analysis identified a total of nine differential metabolites, with four upregulated in the Z17 group and five upregulated in the R1053 group. This study demonstrates that the hybrid variety R1053 has a higher utilization value than the inbred variety Z17, which is closely associated with rumen microbes and metabolites. This study provides new insights into the efficient utilization of rice straw in ruminants from microbiological and metabolomic perspectives.